2016
DOI: 10.1002/cam4.821
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic value of MMP9 activity level in resected stage I B lung adenocarcinoma

Abstract: The clinical outcomes of patients with early‐stage non‐small cell lung cancer (NSCLC) have remained unsatisfactory after complete surgical resection. The objective of this study was to explore the prognostic value of matrix metalloproteinase 9 (MMP9) activity level in Chinese patients with stage I B lung adenocarcinoma. A sensitive and validated method was employed for determining the activity of MMP9 in human lung adenocarcinoma cells in vitro. Then, the association was examined between the level of MMP9 enzy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 33 publications
0
7
0
Order By: Relevance
“…Another study suggested that increased MMP9 expression was associated with gastric cancer cell invasion . In addition, MMP9 activity has been reported to be correlated with prognosis of other cancers, including cancers of the lung, colorectum, esophagus, and breast . Importantly, transcript levels of MMP9 were also observed to be increased in melanoma tumors, compared with that of melanocyte controls .…”
Section: Discussionmentioning
confidence: 99%
“…Another study suggested that increased MMP9 expression was associated with gastric cancer cell invasion . In addition, MMP9 activity has been reported to be correlated with prognosis of other cancers, including cancers of the lung, colorectum, esophagus, and breast . Importantly, transcript levels of MMP9 were also observed to be increased in melanoma tumors, compared with that of melanocyte controls .…”
Section: Discussionmentioning
confidence: 99%
“…Despite improvements in the detection and treatment of early‐stage lung cancer, which may be a result of the increased use of computed tomography (CT), a third of patients with early‐stage lung cancer survive less than five years . This is partially attributable to the limited therapeutic efficacy of surgery, radiation, and chemotherapy in lung cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Association between PKCζ, MMP-2 and MMP-9 expression in lung adenocarcinoma. angiogenesis, invasion and metastasis (26,27). The mechanism underlying this effect involves the increase of VEGF secretion from tumor cells induced by MMP-2 and MMP-9, promoting invasion and metastasis, which is dependent on MAPK activation and ERK phosphorylation.…”
Section: Discussionmentioning
confidence: 99%